13th International Biennial of drawings 1994/95 : Designer's Drawings - Bernik, Stane; 13th International Biennial of drawings, Rijeka 1994/95 (Rijeka : Moderna Galerija, 1995)
Annink, Ed Nizozemska ; Apple Industrial Design Group Sad ; Gemma, Bernal, Ramon Isern, Spajolska ; Budavari, Madarska, Peter ; Burian, Frantisek ; Castiglioni, Achille ; Da Costa, Daciano ; Martinez Afonso Dias, Eduardo Manuel ; Ekuan, Kenji ; Fabijanic Hrvatska, Nenad ; Finkel, Henry ; etc.
13th International Biennial of drawings 1994/95 : Designer's Drawings / 13. mdunarodni Biennale crteza 94/95 : Dizajnerski Crtez, Moderna Galerija, Rijeka, 24.02. - 15.04.1995
boek